2016
DOI: 10.1177/1528083715624258
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal properties of jute and hollow conjugated polyester fibre reinforced non-woven composite

Abstract: Sandwich structure of non-woven composite is produced by using a compressive hot pressing method. It is ranging from 2500 grams per square meter (gsm) to 3500 gsm. Composite sample is designed using Box and Behnken model. Considering 50-70% weight of jute fibre content with 30-50% weight of hollow conjugated polyester fibre, ideal thickness of the composites is maintained in the range from 4 to 5 mm. Thermal properties such as thermal conductivity, thermal resistance, thermal transmittance and thermal diffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Such composite fibers, e.g. concentric core/sheath (Figure 1(a)), eccentric core/sheath (Figure 1(b)), 50/50 side-by-side (Figure 1(c)), unequal side-by-side, (Figure 1(d)), island-in-the-sea (Figure 1(e)), and segmented-pie fibers (Figure 1(f)), are widely manufactured in the textile industry [916]. Zhao and Liu [15] demonstrated that core/sheath fibers could reduce the energy consumption in the following application process, while side-by-side fibers can maintain their three-dimensional heterostructure after hot-stretching processing.…”
Section: Introductionmentioning
confidence: 99%
“…Such composite fibers, e.g. concentric core/sheath (Figure 1(a)), eccentric core/sheath (Figure 1(b)), 50/50 side-by-side (Figure 1(c)), unequal side-by-side, (Figure 1(d)), island-in-the-sea (Figure 1(e)), and segmented-pie fibers (Figure 1(f)), are widely manufactured in the textile industry [916]. Zhao and Liu [15] demonstrated that core/sheath fibers could reduce the energy consumption in the following application process, while side-by-side fibers can maintain their three-dimensional heterostructure after hot-stretching processing.…”
Section: Introductionmentioning
confidence: 99%
“…Plant population: In farmer's plot, MG-1 gave higher plant population (4.60 L ha À1 ) at Chandina station and the lowest plant population (0.92 L Table 4. Physical properties of jute fiber (IJIRA, 2012; Roy and Lutfar, 2012;Pujari et al, 2014;Zakriya et al, 2015;Banerjee et al, 2015;Shahid et al, 2016;Sathishkumar et al, 2017;Khan et al, 2020) ha À1 ) at Monirampur during 2016-17 (Table 9). In respect of means over year, this genotype showed higher plant population (3.40 L ha À1 ) with the mean of 1.63 L plant ha À1 (Table 9).…”
Section: Performance Of Mg-1 Compared To O-795 For Fiber Yield and Yield Related Traits At Farmers' Fieldsmentioning
confidence: 99%
“…57 Juan et al 58 found that jute/polyester resin skins have a thermal conductivity value of 0.092 W/m.K and jute fibre honey comb have a thermal conductivity value of 0.094 W/m.K shown the best performance insulator Value. Zakriya et al 59 in their research work of thermal properties of jute and hollow-conjugated polyester fibre-reinforced nonwoven composite, the thermal conductivity value 0.0193W/m.K is predicted by response surface method graph. 59 A material can be considered as an appropriate thermal insulator if its thermal conductivity is 0.15 W/m.K or less.…”
Section: Parameters For Sound Insulationmentioning
confidence: 99%
“…Zakriya et al 59 in their research work of thermal properties of jute and hollow-conjugated polyester fibre-reinforced nonwoven composite, the thermal conductivity value 0.0193W/m.K is predicted by response surface method graph. 59 A material can be considered as an appropriate thermal insulator if its thermal conductivity is 0.15 W/m.K or less. 60 The technical sectors of composites using bicomponent fibres yield interesting results.…”
Section: Parameters For Sound Insulationmentioning
confidence: 99%